2020
DOI: 10.1002/aps3.11314
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in adapting CRISPR/Cas9 in nongenetic model plant systems

Abstract: The rapid development and application of the CRISPR system in genome editing and other applications clearly illustrate its revolutionary role in biological research. Its massive impact is similar to that of molecular cloning and PCR technologies (Yin et al., 2017). The CRISPR (clustered regularly interspaced short palindromic repeats)-Cas (CRISPR-associated) (see Box 1 for all abbreviations used in this article) system originated from the microbe immune system and was adapted to provide powerful tools to enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 152 publications
0
30
0
Order By: Relevance
“…Our hypothesis requires further study — an effect of pectin metabolism on inflorescence development has not been reported in Asteraceae. With an established CRISPR/Cas9 system in Tragopogon ( Shan et al, 2018 , 2020 ), the functions of related genes (such as genes encoding pectinesterase and polygalacturonase) could be rigorously examined.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis requires further study — an effect of pectin metabolism on inflorescence development has not been reported in Asteraceae. With an established CRISPR/Cas9 system in Tragopogon ( Shan et al, 2018 , 2020 ), the functions of related genes (such as genes encoding pectinesterase and polygalacturonase) could be rigorously examined.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2013 and 2019, CRISPR/Cas9 technology has been successfully used to modify plant species from 45 genera across 24 families ( Shan et al., 2020 ). However, the application of the CRISPR/Cas9 system to genetically alter woody perennials has been limited to only the following 10 species: apple ( Nishitani et al., 2016 ), cacao ( Fister et al., 2018 ), cassava ( Odipio et al., 2017 ), citrus ( Jia et al., 2017 ), coffee ( Breitler et al., 2018 ), grape ( Nakajima et al., 2017 ), kiwifruit ( Wang et al., 2018 ), Parasponia andersonii ( Van Zeijl et al., 2018 ), pomegranate ( Chang et al., 2019 ), and poplar ( Fan et al., 2015 ; Zhou et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Protein synthesis and processing: peptidyl-prolyl cis-trans isomerases, protein disulfide isomerase-like protein precursor, porin, proteasome subunit β type, eukaryotic translation initiation factor 3 subunit I, BiP isoform A/glycine max, cysteine proteinase, outer plastidial membrane protein porin Intracellular traffic, cell structure: protein TOC75, translocon Tic40, profilin Nitrogen metabolism: L-asparaginase Auxin polar transport: stilbene synthase family protein, monothiol glutaredoxin-S17 protein Lignin biosynthesis: cinnamyl alcohol dehydrogenase Pyruvate metabolism and transport: pyruvate carrier protein Du et al (2018) Vitamin B1 metabolism: thiazole biosynthetic enzyme (TAL effector nucleases or TALENs), and clustered regularly interspaced short palindromic repeat/CRISPR-associated protein 9 (CRISPR/Cas9). Among these, TALENs and CRISPR/Cas9 are the preferred SSNs for research purposes (Kanaar et al, 1998;Pastwa and Blasiak, 2003;Smith et al, 2006;Pâques and Duchateau, 2007;Hartlerode and Scully, 2009;Sander et al, 2011;Qi, 2015;Steinert et al, 2016;Malzahn et al, 2017;Shan et al, 2020). The history of gene targeting technologies started in 1988 when the first gene-targeting experiment was performed on tobacco (Nicotiana tabacum) protoplasts (Paszkowski et al, 1988).…”
Section: Gene Editing Using Talen and Crispr/cas Technologiesmentioning
confidence: 99%
“…Subsequently, TALENs were introduced into the group of plant genome editing technologies (Christian et al, 2010). Finally, CRISPR/Cas9 technology has been used in plants such as Arabidopsis thaliana, N. benthamiana, Oryza sativa, and T. aestivum (Li J. F. et al, 2013;Nekrasov et al, 2013;Shan et al, 2013Shan et al, , 2020.…”
Section: Gene Editing Using Talen and Crispr/cas Technologiesmentioning
confidence: 99%
See 1 more Smart Citation